2011
DOI: 10.1080/02791072.2011.605703
|View full text |Cite
|
Sign up to set email alerts
|

National Study of Prescription Poisoning with Psychoactive and Nonpsychoactive Medications in Medicare/Medicaid Dual Enrollees Age 65 or Over

Abstract: The purpose of this study is to assess prescription medication poisoning among psychoactive and nonpsychoactive medications used by elderly (65 years or older) Medicare & Medicaid dual enrollees as well as examine contextual components associated with poisoning. Our primary research goal was to compare medication poisonings among psychoactive medications to nonpsychoactive medications. Our second research goal was to identify components influencing medication poisonings and how they interrelate. The approach u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Most of these cases do not requires intensive medical treatment, but needs caring approach, psychiatric treatment and social assessment. Our findings are consistent with studies that showed the drugs such as psychoactive family and antidepressant family drugs act mainly on central nervous [37]. Most studies showed that suicide is closely associated with mental disorders [38,39].…”
Section: Discussionsupporting
confidence: 93%
“…Most of these cases do not requires intensive medical treatment, but needs caring approach, psychiatric treatment and social assessment. Our findings are consistent with studies that showed the drugs such as psychoactive family and antidepressant family drugs act mainly on central nervous [37]. Most studies showed that suicide is closely associated with mental disorders [38,39].…”
Section: Discussionsupporting
confidence: 93%
“…Possible mechanisms for medication-related poisonings can be summarized as either direct side effects of CNS medications or indirect effects due to drug–drug interactions and disease–drug interactions [ 2 , 9 ]. In addition, accidental overdosing and medication errors are other common reasons in clinical practice of poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that could potentially modify the effect of CNS medications on the risk of unintentional poisoning were identified based on previous literature [ 2 , 6 , 9 ]. The modifying factors in this study included sex, age, comorbidity, neuropsychiatric disease, and concurrent use of other medications.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations